Influence of infill density and number of layers on mechanical properties of 3D printed pla and abs sandwich structures - Mirko Karakašić; Ivan Grgić; Vladimir Perak; , Jure Marijić; Hrvoje Glavaš (Advanced Engineering Letters)
The increasing use of products manufactured by applying additive technologies encourages using materials with better mechanical properties. Depending on the type of material, its initial state, structure and mechanical properties, materials can be categorized differently. Combining polymer materials with different mechanical properties into composite structures makes it possible to obtain materials with better mechanical properties, which are then used on printers based on fused deposition modeling (FDM) 3D printing technology. This paper investigates the mechanical properties of samples made by combining Polylactic Acid (PLA) and Acrylonitrile Butadiene Styrene (ABS) polymer materials. The samples were produced with different proportions of the two materials regarding the number of layers and the infill density. The test was performed according to ISO 527 - 2: 2012 on a Shimadzu AGS-X 10 kN tensile test machine. For comparison, control samples of PLA and ABS materials were printed with 100% infill and showed the highest average force. Samples with a combination of materials did not produce the expected better results than samples made from one material. The reason for this is the occurrence of delamination of individual layers.